Data analysis of online shopping platform during the COVID-19 epidemic of Coronavirus disease - Bin Zhao; Jinming Cao (Archives of Community Medicine and Public Health - Peertechz Publications, 2021)
Data analysis of online shopping platform, and With the development of online platform, more and more consumers will choose this convenient way of online shopping. This paper uses Spyder's time-based model to mine the rating data of Amazon online shopping platform, establishes a neural network model, analyzes the connection relationship of each rating index, carries out descriptive statistical analysis on each index, obtains the correlation results between the impact indicators, and carries out fuzzy evaluation, analyzes the impact of each evaluation index on the product, and finally combines the product's The relationship between sales situation and rating provides reliable product sales design mode for Amazon, and gives some sales suggestions, so as to enhance the product's desirability.